2012
DOI: 10.1258/la.2012.011117
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of mouse fetal weight by ultrasonography: application from clinic to laboratory

Abstract: Ultrasonographic assessment of fetal growth to estimate fetal weight has been widely used in clinical obstetrics but not in laboratory mice. Even though it is important to assess fetal growth abnormalities for gene-targeting studies using mice, there have been no reports of accurately estimated fetal weight using fetal biometric parameters in mice. The aim of this study was to establish an accurate mouse formula using fetal biometric parameters under ultrasound imaging. Using a high-frequency ultrasound system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Because of advances in ultrasound imaging technology, commercially available ultrasound systems now have the spatial and temporal resolution to obtain accurate images of rat and mouse hearts, kidneys and other organs (Coatney 2001;Golden et al 2012;Kobayashi et al 2001;Srinivasan et al 1998;Stypmann 2007). For this reason, ultrasound is a practical method for the diagnosis of pregnancy in agouti mice (Sousa et al 2012), staging of gestation and monitoring of intrauterine growth in rats (Brown et al 2006;Mu et al 2008;Nguyen et al 2012;Pallares and Gonzalez-Bulnes 2009;Ypsilantis et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Because of advances in ultrasound imaging technology, commercially available ultrasound systems now have the spatial and temporal resolution to obtain accurate images of rat and mouse hearts, kidneys and other organs (Coatney 2001;Golden et al 2012;Kobayashi et al 2001;Srinivasan et al 1998;Stypmann 2007). For this reason, ultrasound is a practical method for the diagnosis of pregnancy in agouti mice (Sousa et al 2012), staging of gestation and monitoring of intrauterine growth in rats (Brown et al 2006;Mu et al 2008;Nguyen et al 2012;Pallares and Gonzalez-Bulnes 2009;Ypsilantis et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The EFW formula with an APE less than 10% is considered accurate (Nguyen et al., 2012 ). Among the applied formulas in our study, 10% or less in an APE was present in five formulas, and especially, the Combs formula demonstrated the most outstanding performance capability for estimating the weight of cynomolgus monkey fetuses at approximately 130 GD in our study (Tables 4 and 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy ultrasound examination is common in domestic animals (e.g., horse, cattle, goat, sheep, swine, dog, and cat), laboratory animals (e.g., ferret, guinea-pig, rabbit, and rat), exotic ungulates (e.g., deer, antelopes, anoa, banteng, giraffe, camelids, and rhinoceros), and zoo and wild animals (e.g., primates, dolphin, shark, and opossum) [ 5 ]. Ultrasound examination is used experimentally in some small laboratory animals, such as rabbits [ 6 ], rats [ 7 ], and agoutis [ 8 ]. Some studies have shown the effective use of ultrasound backscatter microscopy in examining the fetal development in mice, in particular the development of the embryonic eye, heart, and central nervous system [ 9 ].…”
Section: Introductionmentioning
confidence: 99%